Levels, temporal trend and health risk assessment of five heavy metals in fresh vegetables marketed in Guangdong Province of China during 2014–2017. (October 2018) - Liang, Hui; Wu, Wei-Liang; Zhang, Yong-Hui; Zhou, Shao-Jun; Long, Chao-Yang; Wen, Jian; Wang, Bo-Yuan; Liu, Zhi-Ting; Zhang, Chao-Zheng; Huang, Pan-Pan; Liu, Ning; Deng, Xiao-Ling; et al.
Abstract: To systematically investigate the presence of toxic heavy metals and evaluate the potential health risks of heavy metals (HMs), the levels of cadmium (Cd), lead (Pb), arsenic (As), mercury (Hg), and chromium (Cr) in a total of 4401 representative samples of highly consumed fresh vegetables sampled from 21 prefecture-level cities of Guangdong Province, China, were determined by inductively coupled plasma mass spectrometry (ICP-MS). In the analyzed vegetables, the heavy metal concentrations exceeded the maximum allowable concentrations (MACs) set by Chinese legislation were of 2.41% for Cd, 1.61% for Pb, 0.55% for As, and 0.48% for Cr. The concentrations of HMs indicated significant differences ( p  < 0.05) in vegetable groups and regions. Cd, and Pb were the major contaminants in vegetables according to the results of principal component analysis. During the four-year survey, a temporary rising trend was observed in As and Cr. The results from hierarchical cluster analysis also demonstrated that the status of HMs contaminations in vegetables from various regions displayed certain changes over time. The health risks associated with the intake of these HMs via vegetable consumption were evaluated in term of estimated daily intake (EDI), and noncarcinogenic and carcinogenic risks by target hazard quotient (THQ) and carcinogenic risk (CR). EDI values of each HM at both common and high consumption levels were observed to be less than the corresponding provisional tolerable daily intakes. The THQs of individual HMs and total target hazard quotients (TTHQs) were less than 1, indicating low health hazards for local residents. However, high consumption of stalk and stem vegetables, leafy vegetables, and root and tuber vegetables, and high consumption of vegetables marketed in the northern region (NR) of Guangdong Province resulted in TTHQs that approach 1 and may cause health risks to increase. The carcinogenic risks (CRs) of Cd, Pb and As were below the threshold level (10 −6 ) or residual level (10 −4 ), suggesting low potential CR from these HM exposures via vegetables consumption. However, highly consumed vegetable categories with high Cd concentrations and vegetables marketed in NR resulted in the CRs of Cd and TCRs exceeding the acceptable range, indicating that serious potential carcinogenic risks to human health may exist. In summary, the findings of this study reveal safe exposures of HMs via vegetable consumption, however, great concern should be focused on the noncarcinogenic and carcinogenic risks associated with high exposures of HMs, especially Cd, Pb and As, via high vegetable intake. Graphical abstract: Image 1 Highlights: Five heavy metal levels in nine vegetable categories were investigated. The major contaminants in vegetables marketed in Guangdong Province were Cd and Pb. Higher consumers may experience the health risks mainly caused by Cd, Pb, and As.